2001
DOI: 10.1063/1.1360784
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature Ohmic contact on n-type GaN with surface treatment using Cl2 inductively coupled plasma

Abstract: A room-temperature Ti/Al Ohmic contact on n-type GaN was obtained by surface treatment using Cl2 inductively coupled plasma treatment. The specific contact resistivity was dramatically decreased from the Schottky behavior to 9.4×10−6 Ω cm2 by the treatment. The binding energy of the Ga–N bond and the atomic ratio of Ga/N were simultaneously increased after the plasma treatment. This provides evidence that N vacancies, acting as donors for electrons, were produced at the etched surface, resulting in a shift of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 9 publications
0
21
1
1
Order By: Relevance
“…For the samples annealed under 400¨600 -C ambient, the point defects could be annealed out, releasing electrons, and thus holes are compensated, leading to higher ohmic contact resistance. The behavior of defects induced by plasma or electron bombardment has been widely observed in compound semiconductor, such as GaN [17,18] and SiGe [19,20]. The sample annealed under 500 -C showed lower ohmic contact resistance than the one under 400 -C. It might be explained by the point defects reactivated under 500 -C annealing temperature, causing an increase of hole concentration and hence the contact resistance was reduced.…”
Section: Resultsmentioning
confidence: 90%
“…For the samples annealed under 400¨600 -C ambient, the point defects could be annealed out, releasing electrons, and thus holes are compensated, leading to higher ohmic contact resistance. The behavior of defects induced by plasma or electron bombardment has been widely observed in compound semiconductor, such as GaN [17,18] and SiGe [19,20]. The sample annealed under 500 -C showed lower ohmic contact resistance than the one under 400 -C. It might be explained by the point defects reactivated under 500 -C annealing temperature, causing an increase of hole concentration and hence the contact resistance was reduced.…”
Section: Resultsmentioning
confidence: 90%
“…To verify this, a reported successfully Ti/Al metal scheme was chosen due to its low work function [18][19][20][21]. Ti helps to improve the adhesion and reacts easily with N forming a TiN interface often even only after deposition [15].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that induced damage in nitride materials may take various forms, leading to changes in their electrical properties [16]. Previous works reported that surface treatments, and in particular plasmabased etching, can significantly improve the quality of ohmic contacts to n-type GaN [17,18]. Si implantation, as well as plasma etching, produces Nitrogen vacancies on the surface, which is desirable for the improvement of contact resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that induced damage in nitride materials may take various forms, leading to changes in their electrical properties [13]. Previous works reported that surface treatments, and in particular plasma-based etching, can significantly improve the quality of ohmic contacts to n-type GaN [14][15]. Si implantation, as well as plasma etching, produces Nitrogen vacancies on the surface, which is desirable for the improvement of contact resistance.…”
Section: Fig 2 Afm Images Of the Implanted Ganmentioning
confidence: 99%